DEVELOPMENT OF THE METHODOLOGY OF USING SPECIAL GAME TASKS IN THE PROCESS OF EDUCATION AND TRAINING OF YOUNG TAEKWONDO PLAYERS - Abdukadirova Runo (Innovate Conferences, 2025)
Until recently, oriental martial arts (including taekwondo) were usually practiced by people with advanced training. Therefore, the initial training methodology in taekwondo was developed without fully taking into account the age characteristics of the participants and without selecting appropriate training methods. Only recently have scientists and educators begun to address this issue.